2008
DOI: 10.1080/13557850701803163
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health knowledge, attitudes and behaviours: variations among a religiously diverse sample of young people in London, UK

Abstract: The findings demonstrate diverse sexual health knowledge, sexual attitudes and sexual behaviours among young people with different religious affiliations. These variations demonstrate the importance of tailoring health education and promotion interventions to meet the specific needs of young people from a variety of different religions. The challenge ahead is to find ways to work with these young people to broach such sensitive issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 28 publications
4
23
1
1
Order By: Relevance
“…Similarly, our results are consistent with research at the individual level showing a negative association between g and religiosity (Bertsch & Pesta, 2009), and a positive association with liberal or progressive social attitudes and leftist political orientations which appears to be partly mediated by education (e.g., Deary et al, 2008;Schoon et al, 2010). Given research showing a negative association between religiosity and attitudes toward sex education, use of contraception methods (e.g., Coleman & Testa, 2008), and abortion (e.g., Petersen, 2001;Zucker, 1999), it is reasonable to hypothesize that lower IQ states are likely to suffer higher rates of teen fertility due to an unwillingness to provide effective sex education, access to contraception methods, and abortion services due in part to their reliance on religious and conservative social attitudes rather than health literacy. Additionally, it is noted that our results based on U.S. states is consistent with previous findings in other countries.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, our results are consistent with research at the individual level showing a negative association between g and religiosity (Bertsch & Pesta, 2009), and a positive association with liberal or progressive social attitudes and leftist political orientations which appears to be partly mediated by education (e.g., Deary et al, 2008;Schoon et al, 2010). Given research showing a negative association between religiosity and attitudes toward sex education, use of contraception methods (e.g., Coleman & Testa, 2008), and abortion (e.g., Petersen, 2001;Zucker, 1999), it is reasonable to hypothesize that lower IQ states are likely to suffer higher rates of teen fertility due to an unwillingness to provide effective sex education, access to contraception methods, and abortion services due in part to their reliance on religious and conservative social attitudes rather than health literacy. Additionally, it is noted that our results based on U.S. states is consistent with previous findings in other countries.…”
Section: Discussionsupporting
confidence: 89%
“…Gould et al reported that the level of knowledge of participants was highly affected by their cultural beliefs and religious issues [14]. The relationship between religion and SRH knowledge has also been reported in another study [16]. Although we did not investigate the effect of religious and cultural factors on the level of SRH knowledge of participants, we suggest that adults participating in our study might have been affected by their culture and hence lacked the necessary information on SRH.…”
Section: Discussioncontrasting
confidence: 40%
“…In fact, more recent studies suggest a more complex relationship between religion and sexual and contraceptive behaviours, which may vary by type of religious affiliation, strength of religious involvement, and population group 8,9 . In particular, the strength of the relationship between sex and religiosity may vary by gender, culture and religious denomination 5,9,10 . Most research has been conducted in the United States, which stands as an outlier among western societies with regard to its relatively higher religiosity.…”
Section: Introductionmentioning
confidence: 99%